2018
DOI: 10.1097/md.0000000000010087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the efficacy and safety of simultaneous splenectomy in liver transplantation patients

Abstract: Background:Simultaneous splenectomy during liver transplantation (LT) is debated. The present meta-analysis assessed the efficacy and safety of splenectomy on the outcome of LT patients.Methods:We searched PubMed, Embase, and Wanfang databases for relevant studies published until the date of July 15, 2017. Quality assessment of the included studies was performed using a modified Newcastle-Ottawa Scale judgment. The data were analyzed using RevMan5.3 software.Results:A total of 16 studies consisting of 2198 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Liver transplantation (LT) has been established as a standard treatment for patients with HCC who meet the Milan criteria. Splenectomized LT patients benefit from increased platelet counts, but they suffer risks, including increased operation time, intraoperative blood loss, intraoperative red blood cell transfusion, and postoperative complications (150). Splenectomy improves patient prognosis but only in a subgroup of patients with an increased neutrophillymphocyte ratio (NLR) and increased infiltration of CD163 + TAMs in the tumor stroma, both of which are indicative of enhanced myelopoiesis (151).…”
Section: Impact Of Splenectomy On Malignancymentioning
confidence: 99%
“…Liver transplantation (LT) has been established as a standard treatment for patients with HCC who meet the Milan criteria. Splenectomized LT patients benefit from increased platelet counts, but they suffer risks, including increased operation time, intraoperative blood loss, intraoperative red blood cell transfusion, and postoperative complications (150). Splenectomy improves patient prognosis but only in a subgroup of patients with an increased neutrophillymphocyte ratio (NLR) and increased infiltration of CD163 + TAMs in the tumor stroma, both of which are indicative of enhanced myelopoiesis (151).…”
Section: Impact Of Splenectomy On Malignancymentioning
confidence: 99%
“…Nonetheless, preoperative rituximab with plasmapheresis and the success of newer generation direct-acting antiviral (DAA) agents have limited the indications for splenectomy in ABO-incompatible and HCV-positive recipients, respectively [7,8]. Furthermore, simultaneous splenectomy (SS) in the context of cirrhosis was reported to negatively affect complications such as prolonged operative time, increased blood loss, portal vein thrombosis, and post-splenectomy sepsis syndrome [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia in HCV-infected patients is thought to be due to portal hypertension-induced splenomegaly, resulting in the splenic pooling of platelets [ 23 ]. Spleen size and thrombocytopenia are thought to be associated, and meta-analyses have shown that splenectomy in addition to hepatectomy or liver transplantation improved thrombocytopenia and/or leukocytopenia compared with hepatectomy or liver transplantation alone [ 24 , 25 ]. Reduced portal hypertension following trans-jugular intrahepatic portosystemic shunt was also found to improve thrombocytopenia [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%